2022
DOI: 10.3389/fonc.2022.1011052
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of self-reported financial toxicity among patients with nasopharyngeal carcinoma undergoing radiotherapy: A cross-sectional study in western China

Abstract: Objective Using the Comprehensive Score for Financial Toxicity (COST) tool to measure financial toxicity (FT) among nasopharyngeal cancer (NPC) patients in western China and investigate the association between FT and psychological distress.MethodsWe conducted a cross-sectional study of survivors with NPC in a tertiary oncology hospital in China. FT was assessed using the COST (Chinese version), a validated instrument widely used both at home and abroad. The NCCN Distress Thermometer (DT) was used to measure ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
1
1
Order By: Relevance
“…Our study confirmed some previously reported risk factors for FT among patients with cancer, 6 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 , 25 , 29 including younger age at diagnosis, unmarried status, lower annual household income, negative impact of cancer on participants' and family caregiver's work, advanced cancer stage, longer hospital stay for cancer treatment or treatment-related side-effects, lack of social medical insurance or having URRBMI, and lack of commercial medical insurance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirmed some previously reported risk factors for FT among patients with cancer, 6 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 , 25 , 29 including younger age at diagnosis, unmarried status, lower annual household income, negative impact of cancer on participants' and family caregiver's work, advanced cancer stage, longer hospital stay for cancer treatment or treatment-related side-effects, lack of social medical insurance or having URRBMI, and lack of commercial medical insurance.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of FT among Chinese patients with cancer is 61%–84%. 9 Studies conducted in one or a few tertiary hospitals within a province have identified factors associated with FT, 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 including income, age, health insurance status, employment status, post-cancer employment changes, educational level, place of residence, cancer stage, treatment plan, and social support. Another study conducted in two tertiary hospitals across two provinces identified urban–rural differences in FT, 22 and an association between enhanced eHealth literacy and a low risk of FT was reported.…”
Section: Introductionmentioning
confidence: 99%
“…found that the severe FT group accounted for a mere 2.4% of patients with nasopharyngeal carcinoma, while the mild and moderate FT groups accounted for 37.1% and 50.5%, respectively. 33 Focusing on older cancer survivors, the percentage in the high profile in our study is much higher than the figure observed in other studies. One study of 31 communities across the U.S. found that only 20% of older adults with advanced cancer experienced FT. 18 Another survey conducted in Mexico found that 0% of older patients with cancer reported severe FT, 52% reported mild FT, 39% reported moderate FT, and 9% reported no FT. 25 In the current study, the mean COST value among the study sample was 12.6 (SD: 9.8).…”
Section: Discussioncontrasting
confidence: 81%
“…This might be because peasants have lower incomes and the capacity to pay, making them less willing to receive trastuzumab or rituximab. [35][36][37] Even though trastuzumab and rituximab are already covered by health insurance, the illness burden remains high. In China, different occupations represent different social classes and income levels.…”
Section: Discussionmentioning
confidence: 99%